(untitled) (Research, Society and Development, 2022)
An individual constructs its identity in a context traversed by ideologies and standards proposed by the culture it belongs to, sometimes recurring to extreme diets, extenuating physical activities, use of medications and other potentially harmful habits to achieve an aesthetic goal. Given the complex development of extreme eating habits and eating disorders, psychosocial factors such as experiences, emotions and daily habits are considered, once these can be predisposing, precipitating, and perpetuating factors of the health-disease process. Considering the routine of medical students and the access to information in the health field, this study proposes analyzing the development of extreme eating habits in young adults studying Medicine in the city of São João del Rei – MG. Using qualitative and quantitative methodologies, seven volunteers were selected from their score in the Eating Attitudes Test (EAT-26). Data was collected through interviews based on Thematic Oral History and five guiding questions. Data analysis followed criteria from Bardin’s Content Analysis. Interviewees considered that their extreme eating habits are linked to social and familiar pressure, compensation mechanisms, guilt, psychiatric phenomena, digital influence, COVID-19 pandemic, and professional assistance. Discourse variations were found when considering these factors positive or negative influences in the development of extreme eating habits.